Synthesis of PEGylated semiconducting polymer amphiphiles for molecular photoacoustic imaging and guided therapy - Xie, Chen (2020)
Semiconducting polymer nanoparticles (SPNs) have been used as a new class of photonic materials with great potential in biomedical applications, but their synthetic method is limited to nanoprecipitation. Semiconducting polymer amphiphiles (SPAs) that can spontaneously self-assemble into nanoparticles are ideal alternatives for SPNs. Depending on their backbone structures, SPAs with different optical properties can be developed into nanoprobes for molecular imaging applications such as photoacoustic (PA) and fluorescence imaging as well as photothermal therapy. In this Concept, recent studies on the synthesis of SPAs for PA imaging and guided cancer therapy are summarized. The effect of grafting density on the optical properties of SPAs is discussed, and the nanoparticle sizes of SPAs can be reduced by utilization of a short semiconducting oligomer. Moreover, SPAs can be developed into PA theranostic platform and activatable PA nanoprobes. These studies demonstrate that SPAs are promising for advanced molecular imaging and therapy applications.